2003
DOI: 10.1097/00008571-200301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A functional single-nucleotide polymorphism in the human cytidine deaminase gene contributing to ara-C sensitivity

Abstract: To test the hypothesis that analyses of drug targets for polymorphism will help to establish gene-based information for the treatment of cancer patients, we investigated the functional single-nucleotide polymorphisms in the human cytidine deaminase (HDCA) gene. The cDNAs from 52 leukaemia/lymphoma samples and 169 control blood samples were direct-sequenced and analysed for the polymorphisms. Three different polymorphisms (A79C, G208A and T435C) were identified in the coding region of the HDCA gene and displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 33 publications
2
74
0
Order By: Relevance
“…CDA 79 A4C encoded for a lysine to glutamine amino-acid change (K27Q) and the SNP published by Yue et al, CDA 208G4A, encodes for an alanine to threonine amino-acid change (A70T). 27 The two SNPs identified in the DCK gene, DCK IVS1-1110T4C and DCK 2190A4T, did not encode for an amino-acid substitution. A synonymous (T4C) SNP at nucleotide 315 was reported in the DCTD gene.…”
Section: Resultsmentioning
confidence: 96%
“…CDA 79 A4C encoded for a lysine to glutamine amino-acid change (K27Q) and the SNP published by Yue et al, CDA 208G4A, encodes for an alanine to threonine amino-acid change (A70T). 27 The two SNPs identified in the DCK gene, DCK IVS1-1110T4C and DCK 2190A4T, did not encode for an amino-acid substitution. A synonymous (T4C) SNP at nucleotide 315 was reported in the DCTD gene.…”
Section: Resultsmentioning
confidence: 96%
“…So far, two nonsynonymous SNPs, 79A4C (Lys27Gln) and 208G4A (Ala70Thr), have been identified in the coding region of the human CDA gene (Yue et al, 2003;Fukunaga et al, 2004;Gilbert et al, 2006;Sugiyama et al, 2007). Ethnic or racial differences in the allele frequencies of these SNPs have been reported, as shown in Table 1.…”
Section: Cytidine Deaminasementioning
confidence: 99%
“…Ethnic or racial differences in the allele frequencies of these SNPs have been reported, as shown in Table 1. Remarkable reduction in activity of 70Thr CDA was reported in vitro (Yue et al, 2003) and in vivo (Sugiyama et al, 2007), while only marginal reduction in activity of 27Gln CDA was observed in vitro (Yue et al, 2003;Gilbert et al, 2006). On the other hand, Fitzgerald et al (2006) investigated SNPs in the promoter region of CDA in vitro and in vivo, and found that some promoter CDA haplotypes might affect CDA activity.…”
Section: Cytidine Deaminasementioning
confidence: 99%
“…However, sensitivity to cytarabine was not changed by introducing homozygous variant CDA Gln 27 Gln polymorphism in this in vitro model. 21 We were unable to assess CDA enzymatic activity using blood samples and correlate it with CDA genotype in this study.…”
Section: Discussionmentioning
confidence: 87%